ANALISIS PENGARUH TASK TECHNOLOGY FIT DAN SATISFACTION TERHADAP CONTINUANCE INTENTION: TELAAH PADA NASABAH LIVIN’ MANDIRI SE- JABODETABEK - Rini Afriani Sinaga; Whony Rofianto (Ibs Press, 2024)
The mobile banking application is an efficient and effective online banking service. However, the use of mobile banking services is still quite limited. One of the contributing factors is the technological task of the mobile banking application that does not meet customer expectations. Thus, this study aims to examine and analyze the relationship between task technology fit and satisfaction in increasing the intention to continue using the Livin' Mandiri mobile banking application. The data in this study were collected from an online survey (questionnaire) taken from the Jabodetabek area. The author uses the PLS-SEM approach in processing data from 96 Bank Mandiri customer respondents. The results of hypothesis testing show that perceived usefulness has not proven to have a positive effect on satisfaction and attitude has not proven to have a positive effect on continuance intention. Meanwhile, the significant results include: task technology fit has a positive effect on perceived usefulness, perceived value has a positive effect on satisfaction, perceived usefulness has a positive effect on continuance intention, perceived usefulness has a positive effect on attitude, and finally satisfaction has a positive effect on continuance intention.